Unprecedented C-F bond cleavage in perfluoronaphthalene during cobaltocene reduction - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Sangole, Mayur; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Singh, Kirandeep; Sen, Sakya S. (DALTON TRANSACTIONS, 2024)

Unravelling the prebiotic origins of the simplest α-ketoacids in cometary ices: a computational investigation - Dash, Soumya Ranjan; Pandya, Rinu; Singh, Geetika; Sharma, Himanshu; Das, Tamal; Haldar, Hritwik; Hotha, Srinivas; Vanka, Kumar (CHEMICAL COMMUNICATIONS, 2024)
Keywords: GLYOXYLATE; Hydrocarbons; Metabolism; Precursors

Unveiling the inverse sandwich complexes of XeO3: a computational exploration - Dash, Soumya Ranjan; Vanka, Kumar (Inorganic Chemistry, 2024)
Our study introduces the design of inverse sandwich (iSw) complexes incorporating a noble gas compound: xenon trioxide (XeO3). Through comprehensive computational analyses, we have investigated the critical factors influencing their stability by employing a variety of state-of-the-art computational tools. We demonstrated that the coordination number of xenon in the iSw complex of XeO3 with 18-crown-6 is influenced by the presence of a rare, weakly stabilizing XeXe interaction between the XeO3 molecules. Furthermore, we observed that the stability of iSw complexes of 1,3,5-triphenylbenzene (TPB) and its derivatives is not solely attributed to aerogen bonding, but also involves contributions from C-HO interactions and back-donation from the lone pair of Xe to the antibonding C-C orbitals of TPB. Additionally, the significant contributions from orbital interactions and dispersion interactions in the TPB derivatives highlight the multifaceted amphoteric properties of XeO3 and reveal that the iSw complexes of TPB and derivatives are not predominantly governed by electrostatic interactions, contrary to conventional belief.